Development and prevention of ischemic contracture (“stone heart”) in the pig heart - Li, Mei; Qin, Zhi; Steen, Erik; Terry, Ann; Wang, Bowen; Wohlfart, Björn; Steen, Stig; Arner, Anders (Frontiers in Cardiovascular Medicine, 2023)
Stone heart (ischemic contracture) is a rare and serious condition observed in the heart after periods of warm ischemia. The underlying mechanisms are largely unknown and treatment options are lacking. In view of the possibilities for cardiac donation after circulatory death (DCD), introducing risks for ischemic damage, we have investigated stone heart in pigs. Following cessation of ventilation, circulatory death (systolic pressure <8 mmHg) occurred within 13.1 ± 1.2 min; and a stone heart, manifested with asystole, increased left ventricular wall thickness and stiffness, established after a further 17 ± 6 min. Adenosine triphosphate and phosphocreatine levels decreased by about 50% in the stone heart. Electron microscopy showed deteriorated structure with contraction bands, Z-line streaming and swollen mitochondria. Synchrotron based small angle X-ray scattering of trabecular samples from stone hearts revealed attachment of myosin to actin, without volume changes in the sarcomeres. Ca2+ sensitivity, determined in permeabilized muscle, was increased in stone heart samples. An in vitro model for stone heart, using isolated trabecular muscle exposed to hypoxia/zero glucose, exhibited the main characteristics of stone heart in whole animals, with a fall in high-energy phosphates and development of muscle contracture. The stone heart condition in vitro was significantly attenuated by the myosin inhibitor MYK-461 (Mavacamten). In conclusion, the stone heart is a hypercontracted state associated with myosin binding to actin and increased Ca2+ sensitivity. The hypercontractile state, once developed, is poorly reversible. The myosin inhibitor MYK-461, which is clinically approved for other indications, could be a promising venue for prevention.